2020
DOI: 10.1016/j.jtrangeo.2020.102818
|View full text |Cite
|
Sign up to set email alerts
|

Disability, wages, and commuting in New York

Abstract: In the U.S., substantial employment and wage gaps persist between workers with and without disabilities. A lack of accessible transportation is often cited as a barrier to employment in higher wage jobs for people with disabilities, but little is known about the intraurban commuting patterns of employed people with disabilities in relation to their wage earnings. Our study compares wages and commute times between workers with and without disabilities in the New York metropolitan region and identifies the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Our analysis adopts the assumption used in the SPM that metropolitan and nonmetropolitan are a reasonable scale for geographic adjustment. Based on work highlighting the variation between costs of living just within the New York City region, it is clear that cost of living is not just variable between metropolitan areas but is quite variable within metropolitan areas (McLafferty & Preston, 2019;Wong et al, 2020). Beyond metropolitan areas, counties in the United States can be quite large and have varying degrees of rurality not captured purely through population size and adjacency to urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis adopts the assumption used in the SPM that metropolitan and nonmetropolitan are a reasonable scale for geographic adjustment. Based on work highlighting the variation between costs of living just within the New York City region, it is clear that cost of living is not just variable between metropolitan areas but is quite variable within metropolitan areas (McLafferty & Preston, 2019;Wong et al, 2020). Beyond metropolitan areas, counties in the United States can be quite large and have varying degrees of rurality not captured purely through population size and adjacency to urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Groups who are not able to drive or take fixed-route public transit and depend on paratransit are much more likely to be denied equal opportunity, full participation in society, independent living, and economic selfsufficiency (11). Wong et al (15) found that in New York, transport options are less accessible and slower for disabled workers than they are for non-disabled workers, and workers with disabilities request higher salaries in exchange for commute times. Brucker and Rollins (16) discovered that workers with disabilities who have similar commute times to workers without disabilities earn substantially less per hour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Transportation and its economic implications in the bay areas require increased academic attention as manufacturing employment has been transferred to the service sectors and this process in bay areas is no exception (Wong et al, 2020). The changes in employment accessibility, to some extent, indicate the degree to which land use and transportation bridge the gap between work possibilities and labor forces.…”
Section: Transportationmentioning
confidence: 99%